Jurassic to Early Cretaceous basin configuration(s) in the Fingerdjupet Subbasin, SW Barents Sea - Serck, Christopher Sæbø; Faleide, Jan Inge; Braathen, Alvar; Kjølhamar, Bent; Escalona, Alejandro (Marine and Petroleum Geology, 2017)
The Fingerdjupet Subbasin in the southwestern Barents Sea sits in a key tectonic location between deep rifts in the west and more stable platform areas in the east. Its evolution is characterized by extensional reactivation of N-S and NNE-SSW faults with an older history of Late Permian and likely Carboniferous activity superimposed on Caledonian fabrics. Reactivations in the listric NNE-SSW Terningen Fault Complex accommodated a semi-regional rollover structure where the Fingerdjupet Subbasin developed in the hangingwall. In parallel, the Randi Fault Set developed from outer-arc extension and collapse of the rollover anticline. N-S to NNE-SSW faults and the presence of other fault trends indicate changes in the stress regime relating to tectonic activity in the North Atlantic and Arctic regions. A latest Triassic to Middle Jurassic extensional faulting event with E-W striking faults is linked to activity in the Hammerfest Basin. Cessation of extensional tectonics before the Late Jurassic in the Fingerdjupet Subbasin, however, suggests rifting became localized to the Hammerfest Basin. The Late Jurassic was a period of tectonic quiescence in the Fingerdjupet Subbasin before latest Jurassic to Hauterivian extensional faulting, which reactivated N-S and NNE-SSW faults. Barremian SE-prograding clinoforms filled the relief generated during this event before reaching the Bjarmeland Platform. High-angle NW-prograding clinoforms on the western Bjarmeland Platform are linked to Early Barremian uplift of the Loppa High. The Terningen Fault Complex and Randi Fault Set were again reactivated in the Aptian along with other major fault complexes in the SW Barents Sea, leading to subaerial exposure of local highs. This activity ceased by early Albian. Post-upper Albian strata were removed by late Cenozoic uplift and erosion, but later tectonic activity has both reactivated E-W and N-S/NNE-SSW faults and also established a NW-SE trend. acceptedVersion publishedVersion